No effect of transcranial direct current stimulation of the dorsolateral prefrontal cortex on short‐term memory - Wang, Jing (CNS Neurosci Ther, 2017)
INTRODUCTION: Short‐term memory refers to the capacity for holding information in mind for a short period of time with conscious memorization. It is an important ability for daily life and is impaired in several neurological and psychiatric disorders. Anodal transcranial direct current stimulation (tDCS) applied to the dorsolateral prefrontal cortex (DLPFC) was reported to enhance the capability of short‐term memory in healthy subjects. However, results were not consistent and what is the possible impact factor is not known. One important factor that may significantly influence the effect of tDCS is the timing of tDCS administration. AIMS: In order to explore whether tDCS impact short‐term memory and the optimal timing of tDCS administration, we applied anodal tDCS to the left DLPFC to explore the modulatory effect of online and off‐line tDCS on digit span as well as visual short‐term memory performance in healthy subjects. RESULTS: Results showed tDCS of the left DLPFC did not influence intentional digit span memory performance, whether before the task or during the task. In addition, tDCS of the DLPFC administered before the task showed no effect on visual short‐term memory, while there was a trend of increase in false alarm when tDCS of the DLPFC administered during the task. CONCLUSIONS: These results did not provide evidence for the enhancement of short‐term memory by tDCS of the left DLPFC in healthy subjects, but it suggested an importance of administration time for visual short‐term memory. Further studies are required to taking into account the baseline performance of subjects and time‐dependence feature of tDCS.